Efficacy and Safety of Immunosuppressive Monotherapy Agents for IgA Nephropathy: A Network Meta-Analysis - Han, Shisheng; Yao, Tianwen; Lu, Yan; Chen, Min; Xu, Yanqiu; Wang, Yi (Frontiers in Pharmacology, 2021)
Background: Efficacy and safety of immunosuppressive monotherapy agents were evaluated for Immunoglobulin A nephropathy (IgAN) using a network meta-analysis approach based on randomized controlled trials (RCTs). Methods: PubMed, Embase, the Cochrane library, and the Web of Science were systematically searched for RCTs published prior to October 1, 2019, using immunosuppressive agents for treating IgAN. Quality assessments were performed according to the Cochrane Handbook. Pooled relative risks (RRs) or standard mean differences (SMDs) with corresponding 95% confidence intervals (CIs) were calculated for discrete or continuous variables, respectively. The primary outcomes were clinical remission, end-stage renal disease (ESRD), and serious adverse events (SAEs). The secondary outcomes were urinary protein excretion and serum creatinine. Data were synthesized using the random-effects model. Results: Twenty-five RCTs with 2005 participants were deemed eligible, and six medications were evaluated: corticosteroids, mycophenolate mofetil (MMF), tacrolimus (TAC), cyclosporine (CsA), leflunomide (LEF), and hydroxychloroquine (HCQ). Compared to supportive care alone, steroids (RR 1.50, 95% CI 1.17–1.93), MMF (RR 2.05, 95% CI 1.15–3.65), TAC (RR 3.67, 95% CI 1.06–12.63), and HCQ (RR 3.25, 95% CI 1.05–10.09) significantly improved clinical remission rates. Only steroids reduced the risk of ESRD (RR 0.35, 95% CI 0.12–0.98), however, SAEs were significantly higher than those of the control group (RR 2.90, 95% CI 1.37–6.13). There was no evidence of different effects of the therapies on serum creatinine levels. MMF showed no significant improvement of remission when excluding studies with follow-up of fewer than two years in the sensitivity analysis (RR 1.41, 95% CI 0.40–4.92). The anti-proteinuric effect of TAC was reversed three months after discontinuing medication; the long-term effects of HCQ could not be evaluated due to the short follow-up. Conclusions: Corticosteroids might induce remission and increase renal survival in IgAN; however, the adverse reactions should be taken into consideration. MMF, TAC, and HCQ might improve remission of proteinuria when treating IgAN, but showed no superiority compared to steroids, and the long-term effects require further study. Registration: PROSPERO, CRD42019147935.